Performance Characteristics of Hedge Funds and Commodity Funds: Natural vs. Spurious Biases - Fung, William; Hsieh, David A. (Journal of Financial and Quantitative Analysis, 2000)
William Fung, David A. Hsieh, Performance Characteristics of Hedge Funds and Commodity Funds: Natural vs. Spurious Biases, The Journal of Financial and Quantitative Analysis, Vol. 35, No. 3 (Sep., 2000), pp. 291-307